2005
DOI: 10.1038/sj.bjc.6602796
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localisation of nuclear factor-kappaB transcription factors in prostate cancer: an immunohistochemical study

Abstract: Several reports suggest that the canonical nuclear factor-kappaB (NF-kB) pathway is constitutively activated in a subset of prostate cancer cells. However, except for RelA (p65), little is known about the status of NF-kB transcription factors in prostate cancer tissues. To clarify the status of NF-kB subunits, we analysed the expression and subcellular localisation of RelA, RelB, c-Rel, p50, and p52 on tissue array sections containing respectively 344, 346, 369, 343, and 344 cores from 75 patients. The subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 24 publications
8
116
2
Order By: Relevance
“…In primary prostate cancer patients, nuclear localization of RelB positively correlates to a patient's Gleason score [100], suggesting that non-canonical activation of RelB may play a significant pathological role in this cancer type. Interestingly, Xu et al [101] found that nuclear localiza-…”
Section: Additional Nf-κb Signaling By Genotoxic Agentsmentioning
confidence: 99%
“…In primary prostate cancer patients, nuclear localization of RelB positively correlates to a patient's Gleason score [100], suggesting that non-canonical activation of RelB may play a significant pathological role in this cancer type. Interestingly, Xu et al [101] found that nuclear localiza-…”
Section: Additional Nf-κb Signaling By Genotoxic Agentsmentioning
confidence: 99%
“…In 2005, high constitutive nuclear levels of RelB were reported in prostate cancer (32). Furthermore, inhibition of RelB in an aggressive prostate cancer cell line significantly reduced the incidence and growth rate of the corresponding tumor xenografts (33).…”
Section: Req Binds To Subunits Of the Swi/snf Complex In Vitro Andmentioning
confidence: 99%
“…Using immunohistochemical studies, it has been demonstrated that all the members of the NF-kB family were expressed by normal prostate tissues, prostatic intraepithelial neoplasia and prostate cancer. However, only the nuclear localization of RelB correlated with the prostate cancer patient's Gleason scores (Lessard et al, 2005), suggesting that the level of RelB is associated with prostate cancer progression. In this study, we examined the role of RelB in prostate cancer cells in response to radiation.…”
mentioning
confidence: 96%